2008
DOI: 10.1007/s00431-008-0672-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of antiepileptic drug therapy on vitamin D status and biochemical markers of bone turnover in children with epilepsy

Abstract: Reports of decreased serum 25-hydroxyvitamin D (25-OHD) and altered bone metabolism associated with antiepileptic drug (AED) treatment are inconsistent and predominantly restricted to adults. In this cross-sectional observational study, the aim was to evaluate the influence of AED treatment on vitamin D status and markers of bone turnover in children with epilepsy. In 38 children taking AEDs and 44 healthy control subjects, blood samples were collected to determine the levels of serum 25-OHD, intact parathyroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
68
4
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(73 citation statements)
references
References 68 publications
0
68
4
1
Order By: Relevance
“…Several studies showed a reduction in 25(OH)D level in epileptic children who had used anticonvulsants for 6 months or more, 19,[28][29][30]32 while others did not. 17,34,36,38,39 These latter studies found this to be the case for non-enzyme-inducing anticonvulsants (valproic acid) use 36,38 or new anticonvulsants (lamotrigine, topiramate, oxcarbazepine, sulthiamine).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies showed a reduction in 25(OH)D level in epileptic children who had used anticonvulsants for 6 months or more, 19,[28][29][30]32 while others did not. 17,34,36,38,39 These latter studies found this to be the case for non-enzyme-inducing anticonvulsants (valproic acid) use 36,38 or new anticonvulsants (lamotrigine, topiramate, oxcarbazepine, sulthiamine).…”
Section: Discussionmentioning
confidence: 99%
“…The subjects consumed valproic acid or carbamazepine as a monotherapy, or in combination with a new anticonvulsant. 29 A cohort study in Greece showed vitamin D deficiency in 49% of subjects. 30 However, that study used a lower definition of vitamin D deficiency (<10 ng/mL), therefore, higher prevalence of vitamin D deficiency was found if a higher definition of vitamin D deficiency (<20 ng/mL) was used, as we did in our study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is not self-evident, though, that these results can be transferred to HIV-infected subjects: for patients on anticonvulsant drugs (which are considered to interfere similarly to ART [1]) and patients with hyperparathyroidism (which was found to occur secondary to ART with tenofovir disoproxil fumarate [5,6]) a loss of seasonality has been described [7,8]. Although a seasonal difference has been hinted at in some small or highly selective HIV-infected populations [9][10][11][12], detailed information is sparse.…”
Section: Seasonal Variations In Vitamin D Levels In Hiv-infected Patimentioning
confidence: 99%